Acute ischemic stroke in a child due to basilar artery occlusion treated successfully with a stent retriever. (6th July 2015) - Savastano, Luis; Gemmete, Joseph J; Pandey, Aditya S; Roark, Christopher; Chaudhary, Neeraj
Abstract : Ischemic strokes in childhood are rare. Thrombolytic therapy with intravenous (IV) tissue plasminogen activator (tPA) has been the main intervention for the management of pediatric stroke patients, but safety data are lacking and efficacy has been questioned. Recently, successful endovascular treatments for acute ischemic stroke in children have been reported with increasing frequency, suggesting that mechanical thrombectomy can be a safe and effective treatment. We present the case of a 22-month-old child with acute ischemic stroke due to basilar artery occlusion that was successfully treated with a stent retriever.